Pengaruh Keaktifan Berorganisasi terhadap Prestasi Akademik Mahasiswa di Unit Kegiatan Kerohanian Universitas Negeri Padang Tahun 2023 - Dina, Rahmat; Sulaiman, Sulaiman (Lembaga Yasin AlSys, 2024)
This research is motivated by the many achievements achieved by students of the Unit Kegiatan Kerohanian, both in academic and non-academic fields. Even though they are active in organizations, this does not reduce the achievements they have achieved. This research aims to: 1) determine the level of student organizational activity in the Padang State University Spiritual Activity Unit in 2023; 2) determine the level of student academic achievement in the Padang State University Spiritual Activity Unit in 2023; and 3) determine the influence of student organizational activity on academic achievement in the Unit Padang State University Spiritual Activities in 2023. This research uses quantitative correlational methods. The population of this study was 60 people. The sampling technique for this research is non-probability sampling, or saturated sampling, namely all 60 UKK students. Data collection was carried out through questionnaires. Data analysis uses hypothesis testing, with organizational activity (X1) as the independent variable and academic achievement (Y) as the dependent variable, using IBM SPSS Statistics 26. Based on the research results obtained through questionnaires, 1) In the F test, there was a result of 8.788 with a significance of 0.004. So Fcount is 8.788>4.001 and sig.0.004<0.05, which means that there is an influence between organizational activity and academic achievement. 2) In the results of the coefficient of determination, there is an R square of 0.132 (13.2%), so there is still an influence of other variables of 86.8%.